The Effect Of Company Size On Audit Delay: The Moderating Role Of Kap's Reputation - Hidayatul Khusnah; Agus Achmad Faisal; Mardiyah Anugraini; Firdeana Fitrotul Ula; Wahidatul Husnaini (Jurnal Bisnis dan Keuangan, 2022)
Financial statements as a form of management's responsibility to investors. Financial reports are a medium of communication between management and parties outside the company. The relevance of the information communicated will be lost if there is a slight delay in submission, therefore financial statements must be presented on time. Financial reports that have been published on the IDX are financial statements that have been audited. Investors in the capital market need financial reports that are reliable, relevant, speedy and timely, easy to understand and can be used as comparisons. Financial performance is used by investors as a basis for making decisions to buy or sell stock assets owned by investors. This study aims to empirically examine the moderating effect of KAP size on the effect of firm size on audit delay of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. This study uses quantitative research and uses financial statement data for food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange from 2016-2021. The data analysis technique in this study used partial least squares (PLS). Based on the results of the study, shows that (1) Firm Size has a significant effect on Audit Delay. (2)KAP's reputation can moderate Company Size against Audit Delay